Chemoselective decarboxylation of ceiba oil to diesel-range alkanes over red mud-based catalyst over H₂-free condition - Nur Athirah Adzahar; N. Asikin-Mijan; Mohd Izham Saiman; G. Abdulkareem Alsultan; M. S. Mastuli; Mohd Razali Shamsuddin; Yap, Taufiq Yun Hin (Royal Society of Chemistry, 2022)
Concerns over global greenhouse gas emissions such as COx and NOx as well as the depletion of petroleum fossil resources have motivated humankind to seek an alternative energy source known as green diesel. In this study, green diesel was produced via a deoxygenation (DO) reaction of ceiba oil under a H2-free atmosphere over Ni modified red mud-based catalysts, which have been synthesized via a precipitation – deep-deposition assisted autoclave method. The obtained catalyst was further characterized by XRF, XRD, BET, FTIR, TPD-NH3, FESEM, and TGA. Based on the catalytic activity test, all Ni/RMOx catalysts facilitated greater DO activity by yielding 83–86% hydrocarbon yield and 70–85% saturated diesel n-(C15 + C17) selectivity. Ni/RMO3 was the best catalyst for deoxygenizing the ceiba oil owing to the existence of a high acidic strength (12717.3 mmol g1 ) and synergistic interaction between Fe–O and Ni–O species, thereby producing the highest hydrocarbon yield (86%) and n-(C15 + C17) selectivity (85%). According to the reusability study, the Ni/RMO3 could be reused for up to six consecutive runs with hydrocarbon yields ranging from 53% to 83% and n-(C15 + C17) selectivity ranging from 62% to 83%.